Uji Aktivitas Antijamur Isolat Bakteri Asam Laktat Dari Fermentasi Sirup Beras Merah Terhadap Candida Albicans Dan Pityrosporum Ovale - Suandy, Suandy; Zendrato, Ronauli Muliani; Chiuman, Linda (Syntax Corporation, 2025)
Lactic acid bacteria (LAB) are known to produce various bioactive metabolites with potential antifungal activity. However, the effectiveness of LAB derived from red rice syrup fermentation against pathogenic fungi has not been extensively studied. This reseach aimed to investigate the antifungal activity of LAB isolates from red rice syrup fermentation against Candida albicans and Pityrosporum ovale. The assay was conducted using the disk diffusion method. Ten LAB isolates were tested for their antifungal activity. Ketocolazole 2% cream was used as the positive control, while distilled water served as the negative control. The results showed that none of LAB isolates were able to inhibit the growth of C. albicans. In contrast, four LAB isolates (SBM 6, SBM 7, SBM 8, and SBM 9) exhibited antifungal activity against P. ovale and produced inhibition zones. The antifungal activity of LAB isolates from red rice syrup appeared to be selective and strain-dependent, indicating their potential as natural antifungal agents, particularly for managing skin disorders caused by Pityrosporum ovale.